ANALISIS KINERJA BANK BERDASARKAN FAKTOR RISK, GOOD CORPORATE GOVERNANCE, EARNING, CAPITAL (RGEC) (Studi pada Bank Campuran periode 2012-2016) - Rizqi Laila Rohmah; Nila Firdausi Nuzula (Jurnal Administrasi Bisnis, 2018)
This research is a quantitative research and using descriptive statistical analysis. This study aims to analyze the performance of Venture Bank 2012-2016 based on the risk, good corporate governance, earning and capital (RGEC) factor. The indicators used are 9 financial ratios and 11 GCG indicators based on Bank Indonesia Regulation Number: 13/1 / PBI / 2011 on Rating of Bank Commercial Rating. This ratio is 4 risk factor ratios, 3 rentability ratios and 2 capital ratios. The result of the research is ​​Bank which has the best performance in risk factor is Bank Paribas, Bank which has the best performance in profitability is Bank Rabobank and Bank that have the best performance in capital is Bank Commonwealth. The Bank with the lowest performance in risk factor is ANZ Bank, the Bank with the lowest performance of profitability and capital is Rabobank Bank. Of all factors, the best performing Bank is the Bank Paribas and the Bank with the lowest performance is Bank Rabobank.  Keywords: Bank Performance, RGEC, Financial Ratios, Venture Banks. АBSTRАK Penelitian ini merupakan penelitian kuantitatif dan menggunakan analisis statistik deskriptif. Penelitian ini bertujuan untuk menganalisis kinerja Bank Campuran tahun 2012-2016 berdasarkan risk, good corporate governance, earning and capital (RGEC). Indikator yang digunakan adalah 9 rasio keuangan dan 11 indikator GCG berdasarkan Lampiran Peraturan Bank Indonesia (PBI) Nomor : 13/1/PBI/2011 Tentang Penilaian Tingkat kesehatan Bank Umum. Rasio ini adalah 4 rasio faktor risiko, 3 rasio rentabilitas dan 2 rasio permodalan.  Hasil penelitian Bank Campuran adalah Bank yang memiliki kinerja terbaik dalam faktor risiko adalah Bank Paribas, Bank yang mempunyai kinerja terbaik dalam rentabilitas adalah Bank Rabobank dan Bank yang mempunyai kinerja terbaik dalam permodalan adalah Bank Commonwealth. Bank yang memiliki kinerja paling rendah dalam faktor risiko adalah Bank ANZ, Bank yang memiliki kinerja paling rendah rentabilitas dan permodalan adalah Bank Rabobank. Dari semua faktor, Bank yang memiliki kinerja paling baik adalah Bank Paribas dan Bank yang mempunyai kinerja paling rendah adalah Bank Rabobank. Kata Kunci: Kinerja Bank, RGEC, Rasio Keuangan, Bank Campuran